Implementasi Literasi Lingkungan di MI Muhammadiyah Gawang Melalui Gerakan Satu Siswa Satu Tanaman - Imtihana, Ezif Rizqi (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to describe the implementation of environmental literacy through the One Student One Plant Movement program at MI Muhammadiyah Gawang. The research method uses a descriptive qualitative approach. Data collection techniques are carried out using questionnaires and documentation. This program is designed through three main stages, namely environmental literacy socialization, program implementation, and plant care assistance. The results of the study indicate that the program is effective in improving students' environmental literacy, evidenced by the average student environmental literacy score of 62.8 before the program (pretest) with a sufficient category and 82.4 after the program (posttest) with a good category, which indicates an increase of 19.6 or 31.2% in environmental literacy scores. This program also contributes to positive changes in student behavior, such as increased awareness of environmental cleanliness and initiatives in caring for plants. Through these activities, students not only gain knowledge about the environment but also real-life experience in maintaining and caring for plants, connecting theory with practice. This program has succeeded in increasing student awareness and involvement in environmental issues, and can be used as a model for similar programs in other schools.